PENINGKATAN PENGETAHUAN ORANGTUA SISWA SDN KREBET TENTANG PENDIDIKAN SEKS PADA ANAK - Dwi Susanti; Khristina Dias Utami; Dwi Yati (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2020)
Background: Increased cases of sexual violence evidance of a lack of children’s knowledge about sex education. Sex education must be given by parents to their children early on, with the aim that children do not misunderstand about sex. The Aim: Is to provide parents with knowledge aboaut sex education in children. The expectation of this activity is the parents of Krebet Elementery School have good knowledgw so that they can properly carry out sex education to their children. Method: The implementation of this activity was carried out in three stage, preparation, implementation and eavluation. The praparation phase includes the preparation of permits, collecting preliminary data by giving a pre-test to parents aboaut sex education for children. The stage of implementation of this activity is to conduct health education about sex education for children. The evaluation stage is to conduct a post-test related to sex education knowledge and make a report on community service activities. Result: The level of knowledge of parents of student before health education was mostly in the sufficient category that is 60%. After health education, an increase in the level of parents knowledge about sex education in the good category. Conclusion: There is an increase in parents’ knowledge about sex education in children after being given health education. Keyword: sex education, children, parents